Performance of green binder developed from flue gas desulfurization gypsum incorporating Portland cement and large-volume fly ash. (19th September 2022) - Wan, Yong; Hui, Xinminnan; He, Xingxing; Li, Jiangshan; Xue, Jianfei; Feng, Dianzhi; Liu, Xiaoli; Wang, Shiquan
Highlights: Developing green binder using FGDG incorporating OPC and large-volume FA. FGDG-based binder has high strength and good water resistance. Evolution law and mechanism of pH value during curing of blended binder were analyzed. Many CSH gels and ettringite were observed on the surface of gypsum crystals by micro tests. Abstract: Flue gas desulfurization gypsum (FGDG) and fly ash (FA) are by-products from coal-fired power plants that urgently need to be recycled in a sustainable way. This study aims to develop a green binder using FGDG incorporating cement and large-volume FA that can substitute some cement in structural and geotechnical engineering applications. The engineering properties including initial setting time, compressive strength, pH value, water absorption and water resistance of the blended binder with different amounts of FGDG were investigated. The results indicate that the addition of FGDG can decrease the initial setting time and water absorption of the blended paste, and is more helpful for the improvement of the early strength. The maximum compressive strength of the blended paste can be obtained when the dosages of FA and cement are the same. When the amount of cement is more than 20%, the softening coefficient of the blended paste was always greater than 0.6 regardless of the amount of FGDG. In addition, the change of pH value with curing time could be divided into four typical stages, which can be explained by the hydration process of the blended binder. Micro-analysis showed that many CSH gels and ettringite were interwoven on the surface of gypsum crystals, which greatly restrained the solubility of gypsum in water and improved the water resistance of the binder.